Static and modalanalysis of Solidarity Bridge in Płock - Bęc, Jarosław; Jukowski, Michał (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
Cable-stayed bridges are stunning structures, which thanks to their dimensions and shapes fascinate not a single observer. Designing such an object is awesome challenge for designers. These structures must transfer forces resulting from dead load, operational loads, temperature changes and coming from wind pressure. Nowadays, each cable-stayed bridge and suspension bridge must be subjected to special analysis to guarantee safe usage. Designers cannot allow the situation, which took place on November 7th,1940 in north-western part of the United States of America near the town Tacoma, where the collapse of the suspension bridge occured. The structure was destroyed as the result of coincidence of natural vibrations and the dynamic wind action. Authors of the paper undertake the task to provide dynamic analysis of Solidarity Bridge in Płock exposed to the wind action. The mentioned structure is the longest cable-stayed bridge in Poland and at the same time, the longest in the world with the arch suspended at one axis to the columnar pylon fixed to a platform. Additionally static analysis is made in order to verify horizontal and vertical displacements as the result of combined variable loads.